MEMINIMUMKAN WAKTU PRODUKSI SANDAL DENGAN PENJADWALAN METODE CDS (Studi pada CV AWMK) - Asni Mustika Rani (Universitas Islam Bandung, 2016)
Scheduling is said to be good when it can meet the needs of companies and consumers feel satisfied. The purpose of scheduling is to minimize the production time and costs, by telling a production facility when to make, with which staff, and on which equipment. Production scheduling aims to maximize the efficiency of the operation and reduce costs. The problem in terms of punctuality causes unfulfilled consumer demand. The purpose of this study is to analyze the current production scheduling in CV AWMK, what methods are used and recommend production scheduling to minimize production time. The results showed that the production scheduling with CDS method can minimize production time, 15 days faster than by using the current production scheduling.